Zwischen Biomacht und Lebensmacht: Biopolitisches Denken bei Michel Foucault und Ernst Jünger - Ahmed, Nasser (transcript, 2021)
The political as a function of struggle: parallels between Michel Foucault's and Ernst Jünger's political thought.